Revolutionizing cervical cancer treatment: single-cell sequencing of TSPAN1+ tumor EPCs and immune checkpoints to assess drug sensitivity and optimize therapy - Li, Yumeng; Lin, Zhiheng; Lin, Guangyao; Zhao, Zhijie; Xiahou, Zhikai; Cai, Pingping (Frontiers in Immunology, 2025)
BackgroundCervical cancer’s tumor microenvironment (TME) was composed of a diverse array of immune cells that significantly influence tumor progression and response to treatment. Recent advancements in multi-omics and single-cell sequencing had provided valuable insights into the cellular heterogeneity and immune landscape of the TME, revealing critical interactions that shape tumor behavior and therapy outcomes.MethodThis study used multi-omics and single-cell sequencing to explore the immune landscape, cellular heterogeneity, and drug sensitivity in cervical cancer, focused on tumor subtypes and their interactions with immune cells, and aimed to understand therapy responses.ResultsThe research presented a thorough single-cell analysis of cervical cancer, identified distinct tumor epithelial cell (EPC) subtypes, and explored their roles in tumor progression, immune evasion, and therapeutic response. It underscored the potential of tumor EPCs as valuable biomarkers for prognosis and as targets for personalized treatment approaches.ConclusionThe immune landscape of cervical cancer and its interaction with tumor endothelial progenitor cells played crucial roles in determining the tumor’s progression and response to therapy. The classification of tumor subtypes based on immune characteristics and drug sensitivity was critical for personalized treatment. The identification of TSPAN1 as key biomarkers provided insight into tumor biology and potential therapeutic targets. Our findings emphasized the need for combining immune checkpoint modulation with precise drug sensitivity analysis to optimize treatment strategies, particularly in advanced cervical cancer.